Contrasting patterns of evolution following whole genome versus tandem duplication events in Populus - Rodgers-Melnick, Eli; Mane, Shrinivasrao P.; Dharmawardhana, Palitha; Slavov, Gancho T.; Crasta, Oswald R.; Strauss, Steven H.; Brunner, Amy M.; DiFazio, Stephen P. (Genome Research, 2011)
Comparative analysis of multiple angiosperm genomes has implicated gene duplication in the expansion and diversification of many gene families. However, empirical data and theory suggest that whole-genome and small-scale duplication events differ with respect to the types of genes preserved as duplicate pairs. We compared gene duplicates resulting from a recent whole genome duplication to a set of tandemly duplicated genes in the model forest tree Populus trichocarpa. We used a combination of microarray expression analyses of a diverse set of tissues and functional annotation to assess factors related to the preservation of duplicate genes of both types. Whole genome duplicates are 700 bp longer and are expressed in 20% more tissues than tandem duplicates. Furthermore, certain functional categories are over-represented in each class of duplicates. In particular, disease resistance genes and receptor-like kinases commonly occur in tandem but are significantly under-retained following whole genome duplication, while whole genome duplicate pairs are enriched for members of signal transduction cascades and transcription factors. The shape of the distribution of expression divergence for duplicated pairs suggests that nearly half of the whole genome duplicates have diverged in expression by a random degeneration process. The remaining pairs have more conserved gene expression than expected by chance, consistent with a role for selection under the constraints of gene balance. We hypothesize that duplicate gene preservation in Populus is driven by a combination of subfunctionalization of duplicate pairs and purifying selection favoring retention of genes encoding proteins with large numbers of interactions.
10.1101/gr.125146.111